Analysis of vaccine responses after anti-CD20 maintenance in B-cell lymphoma in the Balearic Islands. A single reference center experience - Gutierrez, Antonio; Alonso, Aser; Garcia-Recio, Marta; Perez, Sandra; Garcia-Maño, Lucia; Martinez-Serra, Jordi; Ros, Teresa; Garcia-Gasalla, Mercedes; Ferrer, Joana; Vögler, Oliver; Alemany, Regina; Salar, Antonio; et al. (Frontiers in Immunology, 2023)
The use of maintenance approaches with anti-CD20 monoclonal antibodies has improved the outcomes of B-cell indolent lymphomas but may lead to significant peripheral B-cell depletion. This depletion can potentially hinder the serological response to neoantigens. Our objective was to analyze the effect of anti-CD20 maintenance therapy in a reliable model of response to neoantigens: SARS-CoV-2 vaccine responses and the incidence/severity of COVID-19 in a reference hospital. In our series (n=118), the rate of vaccination failures was 31%. Through ROC curve analysis, we determined a cutoff for SARS-CoV-2 vaccine serologic response at 24 months from the last anti-CD20 dose. The risk of severe COVID-19 was notably higher within the first 24 months following the last anti-CD20 dose (52%) compared to after this period (just 18%) (p=0.007). In our survival analysis, neither vaccine response nor hypogammaglobulinemia significantly affected OS. While COVID-19 led to a modest mortality rate of 2.5%, this figure was comparable to the OS reported in the general immunocompetent population. However, most patients with hypogammaglobulinemia received intravenous immunoglobulin therapy and all were vaccinated. In conclusion, anti-CD20 maintenance therapy impairs serological responses to SARS-CoV-2 vaccines. We report for the first time that patients during maintenance therapy and up to 24 months after the last anti-CD20 dose are at a higher risk of vaccine failure and more severe cases of COVID-19. Nevertheless, with close monitoring, intravenous immunoglobulin supplementation or proper vaccination, the impact on survival due to the lack of 2 This is a provisional file, not the final typeset article serological response in this high-risk population can be mitigated, allowing for the benefits of anti-CD20 maintenance therapy, even in the presence of hypogammaglobulinemia.